Diagnostic value and clinical significance of high-resolution ultrasonography compared to magnetic resonance imaging in diagnosing temporomandibular joint dislocation: a systematic review - Salamah, Thariqah; Harefa, Glancius Nironsta (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Temporomandibular joint (TMJ) dislocation is uncommon, yet it is associated with a significant negative effect on the patient’s quality of life. Magnetic resonance imaging (MRI), a gold standard for diagnosing TMJ dislocation, is expensive, time-consuming, and cannot be performed on patients with pacemakers and metallic prostheses. On the other hand, high-resolution ultrasonography (HRUS) has low cost, high accessibility, and is less time-consuming. This study aimed to compare the accuracy and reliability of HRUS to MRI in diagnosing TMJ dislocation. METHODS A comprehensive literature search was conducted using PubMed, Cochrane Library, ScienceDirect, and EBSCOhost databases. Keywords such as temporomandibular joint dislocation, temporomandibular displacement, MRI, and ultrasonography were utilized for the search. The articles obtained were then selected based on the inclusion and exclusion criteria, and the quality assessment was conducted using the QUADAS-2 tool. RESULTS 5 studies were included in this systematic review. The critical appraisal results showed sensitivity ranging from 74.3–93.7%, specificity from 84.2–100%, positive predictive value from 68.2–100%, negative predictive value from 64.0–98.3%, and accuracy from 77.7–91.7% of HRUS compared to MRI. CONCLUSIONS HRUS is a reliable method for diagnosing TMJ dislocation. However, MRI is still necessary in selected and more advanced cases.